Studi Fenomenologi Hasil Pemilu Partai Demokrasi Indonesia Perjuangan di Kota Bengkulu Pemilu 2014 dan 2019 - Junaidi Arfian (Jurnal Komunikasi dan Budaya, 2020)
This study aims to analyze the phenomenology of the results of the vote acquisition and PDI Perjuangan seats in Bengkulu City in the 2014 and 2019 Legislative Elections in the Bengkulu City DPRD, which continued to decline in every election since 1999, PDI Perjuangan as the party winning the election nationally is inversely proportional to the acquisition of seats Legislative and votes for PDI Perjuangan in Bengkulu City DPRD, PDI Perjuangan in Bengkulu City in the 2014 and 2019 Legislative Elections only got 1 (one) chair in Bengkulu City DPRD. This research was conducted with a phenomenological study with qualitative methods and SWOT analysis, data analysis was carried out in stages: data collection, data reduction, data presentation and drawing conclusions, this study uses primary data that is the results of interviews with informants - research information and secondary data collected from institutions related to this study, the results of votes and chair, PDI Perjuangan Candidate List (DCT) in the 2014 and 2019 elections. The results showed that the results of the acquisition of chair and votes PDI Perjuangan Bengkulu City that continues to decline in the 2014 and 2019 elections because it was caused by the recruitment of legislative candidates who did not meet the total allocation in each Electoral District in Bengkulu City, the PDI Perjuangan DPC management was unable to meet the maximum chair quota allocation and recruited qualified legislative candidates as votes, both internal and external PDI Perjuangan.